Structural interpretation of Joya Mair oil field, south Potwar, Upper Indus Basin, Pakistan, using 2D seismic data and petrophysical analysis - Zahid, Muhammad; Khan, Asad; Rashid, Mehboob ur; Saboor, Abdus; Ahmad, Sajjad (Journal of Himalayan Earth Sciences, 2014)
The Joya Mair oil field lies in the south-southeast of the Salt Range-Potwar Foreland Basin (SRPFB). It is the result of Tertiary Himalayan collision between the Indian and Eurasian Plates. The SRPFB represents the Precambrian to Recent rocks of the Indian Plate which covers an area of about 2250 Km2. The Himalayan thrusting and folding formed the structural traps in SRPFB. Seismic interpretation has resulted in time and depth contour map, which helps to understand the subsurface structural geometry. Seismic interpretation of the 2D data reveals that the study area has undergone severe deformation illustrated by the development of thrusts and backthrusts. The Joya Mair structure appears to be an open anticlinal structure on the surface. It is a combination of thrust and backthrust, forming a triangle zone in the subsurface. The general trend of these structures is northeast-southwest which is indicative of the fact that the area was subject to southeast northwest compressive stress. The decollement surface is provided by the Salt Range Formation. The reservoir rocks are of Eocene age that occurs at a depth of ~2023 m as interpreted from seismic data. The petrophysical analysis of Minwal X-1 well is done on the basis of well logs which gives approximately 75% hydrocarbon saturation in the reservoir rocks.